The interaction of salinity and light regime modulates photosynthetic pigment content in edible halophytes in greenhouse and indoor farming - Fitzner, Maria; Schreiner, Monika; Baldermann, Susanne (Frontiers in Plant Science, 2023)
Given its limited land and water use and the changing climate conditions, indoor farming of halophytes has a high potential to contribute significantly to global agriculture in the future. Notably, indoor farming and classical greenhouse cultivation differ in their light regime between artificial and solar lighting, which can influence plant metabolism, but how this affects the cultivation of halophytes has not yet been investigated. To address this question, we studied the yield and content of abscisic acid, carotenoids, and chlorophylls as well as chloride of three halophyte species (Cochlearia officinalis, Atriplex hortensis, and Salicornia europaea) differing in their salt tolerance mechanisms and following four salt treatments (no salt to 600 mM of NaCl) in two light regimes (greenhouse/indoor farming). In particular, salt treatment had a strong influence on chloride accumulation which is only slightly modified by the light regime. Moreover, fresh and dry mass was influenced by the light regime and salinity. Pigments exhibited different responses to salt treatment and light regime, reflecting their differing functions in the photosynthetic apparatus. We conclude that the interaction of light regime and salt treatment modulates the content of photosynthetic pigments. Our study highlights the potential applications of the cultivation of halophytes for indoor farming and underlines that it is a promising production system, which provides food alternatives for future diets.